The effect of COVID-19 on online grocery sales: Taylor Farms - Sprandel, Heather (Henry Stewart Talks, 2021)
Surge in online grocery sales, Political factors, Economic factor, Social-cultural factors, Technological factors, Environmental factors, PESTE analysis